African Mahogany Under Saline Stress: An Analysis of the Transpiration Response at Different Salinity Levels - Willian Viana Campos; José Teixeira Filho; Alcebíades Rebouças São José (Plants)
Agriculture in semi-arid regions faces significant challenges due to water scarcity and soil salinity, conditions exacerbated by inadequate irrigation practices and high evaporation rates. African mahogany (Khaya senegalensis), a species valued for its high-quality wood, holds potential for cultivation in these regions, provided that appropriate management practices are adopted. This study investigated the leaf transpiration response of African mahogany seedlings subjected to seven levels of irrigation water salinity, ranging from 0.5 to 5 dS·m−1, using drainage lysimeters in an experimental field in Bahia. Data collection included measurements of stomatal conductance and photosynthetically active radiation (Qleaf) over a four-month period. The results showed a significant reduction in transpiration with increasing salinity, particularly above 3.5 dS·m−1. Regression analyses highlighted a negative correlation between electrical conductivity and leaf transpiration, demonstrating the impact of water quality on plant physiology. These findings underscore the potential of African mahogany for cultivation in semi-arid regions, provided that efficient management practices are implemented to promote sustainable water use and mitigate the effects of salinity.